Inhibition of GSK3 Phosphorylation of β-Catenin via Phosphorylated PPPSPXS Motifs of Wnt Coreceptor LRP6 - Wu, Geng; Huang, He; Abreu, Jose Garcia; He, Xi (PLOS ONE, 2009)
The Wnt/β-catenin signaling pathway plays essential roles in cell proliferation and differentiation, and deregulated β-catenin protein levels lead to many types of human cancers. On activation by Wnt, the Wnt co-receptor LDL receptor related protein 6 (LRP6) is phosphorylated at multiple conserved intracellular PPPSPXS motifs by glycogen synthase kinase 3 (GSK3) and casein kinase 1 (CK1), resulting in recruitment of the scaffolding protein Axin to LRP6. As a result, β-catenin phosphorylation by GSK3 is inhibited and β-catenin protein is stabilized. However, how LRP6 phosphorylation and the ensuing LRP6-Axin interaction lead to the inhibition of β-catenin phosphorylation by GSK3 is not fully understood. In this study, we reconstituted Axin-dependent β-catenin phosphorylation by GSK3 and CK1 in vitro using recombinant proteins, and found that the phosphorylated PPPSPXS peptides directly inhibit β-catenin phosphorylation by GSK3 in a sequence and phosphorylation-dependent manner. This inhibitory effect of phosphorylated PPPSPXS motifs is direct and specific for GSK3 phosphorylation of β-catenin at Ser33/Ser37/Thr41 but not for CK1 phosphorylation of β-catenin at Ser45, and is independent of Axin function. We also show that a phosphorylated PPPSPXS peptide is able to activate Wnt/β-catenin signaling and to induce axis duplication in Xenopus embryos, presumably by inhibition of GSK3 in vivo. Based on these observations, we propose a working model that Axin recruitment to the phosphorylated LRP6 places GSK3 in the vicinity of multiple phosphorylated PPPSPXS motifs, which directly inhibit GSK3 phosphorylation of β-catenin. This model provides a possible mechanism to account, in part, for inhibition of β-catenin phosphorylation by Wnt-activated LRP6.